The Importance of Identity in the Retention and Attainment of Aboriginal Students at Secondary School: some research findings - Russell, Diane (The Australian Journal of Indigenous Education, 1999)
Although the retention rate of Aboriginal students has improved over the past fifteen years, it is still significantly less than that for all other students. In fact, very few Aboriginal students are completing twelve full years of schooling. The situation is worse in country schools than in large metropolitan areas. Despite the fact that some Aboriginal students do stay at school and succeed, very little work has been done to identify what factors have helped those Aboriginal students who have done so. In addition, there is relatively little knowledge about how the various school, home, ability and personal factors are interrelated.